Efficient design of exhaust gas cooler in cold EGR equipped diesel engine - Ghassembaglou, Nasser; Torkaman, Leila (Elsevier BV, 2016)
Using cold EGR method with variable venturi and turbocharger has very significant effect, simultaneously on the reduction of NOX and grime simultaneously. EGR cooler is one of the most important parts in the cold EGR circuit. In this paper optimum design of cooler for working in different percentages of EGR, besides determination of optimum temperature of exhausted gases, efficiency growth, weight reduction, dimension and expenditures reduction, sediment reduction, and optimum performance by using gasoil which has significant amounts of brimstone, is investigated and optimized.
Keywords: Engineering, Chemical; Engineering, Civil; Cooler; Engineering, Environmental; Engineering, Electrical & Electronic; NOX; Engineering, Marine; Physics, Applied; Engineering, Mechanical; Cold EGR; Physics, Nuclear; Architecture; Computer Science, Interdisciplinary Applications; Materials Science, Textiles; Engineering(all)